Volcanic materials as carriers for the formulation of mycoinsecticides using the fungus Beauveria bassiana - Sy, Victoria (2016)
Improvements in the formulation of biological insecticides are crucial to increase their stability and competitiveness in the market. The aim of this work was to evaluate the use of volcanic materials with different hydric retention capacities to increase the thermotolerance of B. bassiana conidia. Two pyroclastic rocks and a zeolite clinoptilolite were selected for this study. In addition, a commercial silica gel was used due to its reported capacity to increase conidial thermotolerance. Dry conidia were mixed with the materials to obtain a 2% w/w granular formulation, while conidial powder alone served as the control. Mixtures were stored at room temperature for 30 days and then exposed to 50 ºC for two hours, and the viability was measured before and after the thermal exposure. No significant decrease in viability was observed for conidia stored with any of the pyroclastic materials, while the germination was reduced by 10, 17 and 23% for unformulated conidia, conidia stored with silica gel and conidia stored with zeolite, respectively. From these results, a pyroclastic rock was selected to test its capacity to maintain high viability under different temperatures (4, 25 and 35 ºC) and humidities (~0 and 20%). A decrease in viability was observed with an increase of temperature, and lower viability was also recorded in humid treatments, but only at 25 and 35 ºC.